Aplikasi Monitoring Persediaan Stok Obat berbasis Web pada UPT Puskesmas Karang Rejo Menerapkan Framework Laravel - Xenna Agustina; Zulfahmi Syahputra; Barany Fachri (Jurnal Nasional Teknologi Komputer, 2026)
The development of information technology has had a significant impact on various sectors, including the healthcare sector. Managing drug inventory manually has the potential to cause various problems, such as recording errors, delayed reporting, stock data discrepancies, and undetected drugs approaching their expiration dates. Based on observations at the UPT Puskesmas Karang Rejo (Karang Rejo Public Health Center), the drug stock management process still relies on logbooks and Microsoft Excel, which prevents the inventory monitoring process from running optimally. This study aims to design and develop a web-based drug stock inventory monitoring application using the Laravel Framework. The system development method used is the System Development Life Cycle (SDLC) with the Waterfall model, which consists of the stages of requirements analysis, system design, implementation, testing, and maintenance. The system is built using the PHP programming language with the Laravel Framework and a MySQL database. The results of the study show that the developed application is capable of assisting in the integrated management of incoming and outgoing drug data, providing real-time inventory reports, and delivering notifications for minimum stock levels and drug expiration dates. The implementation of this system is expected to improve work efficiency, data accuracy, and the quality of healthcare services at UPT Puskesmas Karang Rejo.